Multilingualism, Afrikaans and normative political theory - Duvenage, Pieter (Acta Academica: Critical views on society, culture and politics, 2006)
This contribution focuses on the survival of Afrikaans within the framework of a multilingual South Africa. The first section provides a brief historical reconstruction of the power-political shifts that Afrikaans underwent between 1966 and 2004. In the second section some of the arguments that were used for and against Afrikaans between 1994 and 2004 are presented. In the last section these arguments are shifted to the terrain of contemporary normative political theory, where three aspects are important: the question of addressing language loss in the world; the importance of multicultural citizenship, and the need for a more profound and multilingual understanding of democracy. In short: a democracy is not just characterised by the instrumental counting of votes, but also by the qualitative articulation of different voices.